Effectiveness of using kahoot-assisted interactive video-based learning media on junior high school students' understanding of mathematical concepts - Rijal Sulthon; Deni Efendi; Fungky Marian; Korhan Cengiz (Universitas Muhammadiyah Lampung, 2026)
This study aims to determine the effectiveness of using interactive video based learning media assisted by Kahoot in improving students understanding of mathematical concepts. This research employed a quantitative approach with a one-group pretest-posttest design. The participants were 21 seventh-grade students of SMP Muhammadiyah Way Sulan. The data were collected using a mathematical concept comprehension test consisting of five essay questions. The results of the Wilcoxon Signed Rank Test indicated a significant difference between the pretest (mean = 36.0) and posttest (mean = 87.6) scores with an Asymp. Sig (2-tailed) value of 0.000 < 0.05. This finding suggests that the use of interactive video-based learning media assisted by Kahoot is effective in improving students understanding of mathematical concepts. Therefore, interactive learning media can serve as an alternative instructional strategy to enhance students engagement and learning outcomes in mathematics.